Potential Use of Polymeric Particles for the Regulation of Plant Growth - Pereira, Anderson E. S. [UNESP]; Sousa, Bruno T.; Iglesias, María J.; Alvarez, Vera A.; Casalongué, Claudia A.; Oliveira, Halley C.; Fraceto, Leonardo F. [UNESP] (Springer Nature, 2019)
Plant growth regulators (PGRs) are molecules widely applied in the agriculture, leading to increased crop yield and improved quality of agricultural products. These compounds act as plant hormones, affecting the plant hormonal homeostasis, and thus control plant growth and development. Recently, the development of polymer-based modified release systems for PGRs has emerged as a promising alternative for increasing the efficacy of these compounds. This review will focus on polymeric particles that are used as carrier systems for PGRs, allowing their controlled release and protecting them from degradation. Successful examples include the phytohormone gibberellic acid(GA3)-loaded nanoparticles, which showed higher efficacy than the non-nano active ingredient in promoting seed germination and seedling growth, and salicylic acid (SA) and nitric oxide (NO)-releasing nanoparticles as effective plant protection agents against stresses. Polymeric nanomaterials per se such as chitosan (Cs) can also alter plant signaling pathways and promote plant growth and development. Despite their great potential in improving the plant production with less damage to the environment, relatively few studies have focused on the use of these nanomaterials for the development of modified release systems for PGRs. In this scenario, this review discusses on the major advances and obstacles in the area.
Keywords: Carrier system; Chitosan; Nanoparticles; Plant growth regulator